2003
DOI: 10.1242/jcs.00749
|View full text |Cite
|
Sign up to set email alerts
|

The formation of vault-tubes: a dynamic interaction between vaults and vault PARP

Abstract: tube-like structures in the cytoplasm. Raising the temperature could reverse this process. When the vaulttubes were formed, there were fewer or no VPARP-rods present in the cytoplasm, suggesting an incorporation of the VPARP into the vault-tubes. MVP molecules have to interact with each other via their coiled-coil domain in order to form vault-tubes. Furthermore, the stability of microtubules influenced the efficiency of vault-tube formation at 21°C. The dynamics and structure of the tubes were examined using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
42
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 27 publications
7
42
0
Order By: Relevance
“…As you move outwards towards the cell periphery the number of MVP puncta diminishes. A similar staining pattern has been described with other MVP antibodies (Kedersha et al, 1990;Kickhoefer et al, 1999;van Zon et al, 2003). When potassium tellurite (K 2 TeO 3 ) is added to the culture medium, MVP is no longer concentrated near the nucleus.…”
Section: Mvp Aggregates Form In Response To Telluritesupporting
confidence: 75%
“…As you move outwards towards the cell periphery the number of MVP puncta diminishes. A similar staining pattern has been described with other MVP antibodies (Kedersha et al, 1990;Kickhoefer et al, 1999;van Zon et al, 2003). When potassium tellurite (K 2 TeO 3 ) is added to the culture medium, MVP is no longer concentrated near the nucleus.…”
Section: Mvp Aggregates Form In Response To Telluritesupporting
confidence: 75%
“…Two recent reports show the transport of MVP along microtubules (39,50). It is, however, important to note that all these studies have in common that it is just a smaller fraction of vaults that is found in these associations, and indeed, most vaults seem to freely diffuse in the cytoplasm at a rate that is consistent with their large size (27). We fail to see any gross disruptions of the microtubular network on MVP depletion, which argues that MVP does not influence its overall integrity.…”
Section: Discussionmentioning
confidence: 93%
“…MVP and MVP-green fluorescent protein (GFP) cDNA expression constructs were described elsewhere (27). Transfections were done as described previously (28).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PARP-4 is incorporated into vaults, RNAcontaining subcellular particles in the cytoplasm [55]. Furthermore, ZAP, a human antiviral protein comprising a C-terminal PARP-like domain devoid of catalytic activity, has been shown to exhibit antiviral activity on alphaviruses [56], which contain an Xdomain similar to that of coronaviruses [23,27,28].…”
Section: Discussionmentioning
confidence: 99%